Chinese expert consensus on neoadjuvant and conversion therapies for hepatocellular carcinoma - Zhao, Hai-Tao; Cai, Jian-Qiang (World journal of gastroenterology : WJG, 2021)
The low resection and high recurrence rates in hepatocellular carcinoma (HCC) are the major challenges to improving prognosis. Neoadjuvant and conversion therapies are underlying strategies to overcome these challenges. To date, no guideline or consensus has been published on the neoadjuvant and conversion therapies in HCC. Recent studies showed that neoadjuvant therapy for resectable HCC and conversion therapy for unresectable HCC are safe, feasible, and effective. Neoadjuvant and conversion therapies have the following advantages in treating HCC: R0 resection with sufficient volume of future liver remnant, relatively simple operation, and wide applicability. Therefore, it was necessary to conduct a widely accepted consensus among the experts in China who have extensive expertise and experience in treating HCC using neoadjuvant and conversion therapies, which is important to standardize the application of neoadjuvant and conversion therapies for the management of HCC. The strategies of neoadjuvant therapy include the selection of the eligible patients, therapy regimen, cycles, effect evaluations, and multidisciplinary treatment. The management of patients with insufficient volume of future liver remnant and patients who cannot achieve R0 resection is the key to the strategies of conversion therapy. Here, we present the resultant evidence- and experience-based consensus to guide the application of neoadjuvant and conversion therapies in clinical practice.